Influencia de la densidad de corriente y ph, para evaluar la remoción del Cr+3 y DQO en efluente de etapa de curtido, mediante electrocoagulación fotovoltaica - Diego Pérez, Amilcar Santos (2019)
The present investigation studied the influence of pH and current density in electrocoagulation. Design parameters such as distance between electrodes, reactor volume, dimensions of the electrodes, have been defined by background. For the tests, the pH and the current density of each electrocoagulation were controlled. From the above, was obtained that at pH of 8 and current density of 28.51 mA / cm2 there was a reduction of 71.48% and 99.17% of COD and Cr3+ respectively. With the operating conditions of the data, a photovoltaic panel (PFV) was implemented to electrocoagulation, reporting COD removal results of 66.61% and 79.5% for Cr3+. In terms of energy consumption, in the EC + PFV results of 36.58 kwh/m3 were obtained, and 43.93 kwh/m3 in EC